PENURUNAN ION Fe DAN Mn AIR TANAH KOTA BANJARBARU MENGGUNAKAN TANAH LEMPUNG GAMBUT SEBAGAI ADSORBEN - Agus Mirwan; Hesti Wijayanti (Universitas Lambung Mangkurat, 2011)
Indonesia, particularly Kalimantan island has abundant source of clay peat (CP). CP found as soil grain which is composed by silicon-oxygen tetrahedral and aluminium-oxygen octahedral essential form of very fine mineral. CP has ability in color removal, reducing organic matter and heavy metals which are dissolved in water through adsorption process. This research investigated the influence of adsorbent from natural peat clay, physical activated natural peat clay and chemical activated natural peat clay with CP depth parameter (2, 3 and 4 meters from the soil surface) in adsorbing Fe and Mn from Banjarbaru groundwater. The chemical activation was done by contacting the clay peat with 0.25 M HCl , while the physical activation by burning clay peat in furnace with a temperature of 600oC for 4 hours This research conducted by contacting the adsorbent with 1liter of water from Rambai well for 300 minutes. The results showed that the clay peat based on physical activation at a depth of 3 m gave the optimum conditions in reduction Fe, as shown from the values obtained was 0.27 mg/L, whereas chemical activation at a depth of 2 m could reduce Mn to be 0.081 mg/L.